PENGARUH KUALITAS LAYANAN, FASILITAS DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL “ANEKA MOTOR SERVICE” WARU - SIDOARJO - Shindu Hargo Dedali (Universitas Merdeka Madiun, 2022)
ABSTRACT In an era of very difficult progress, more and more companies are competing to get a good market segment to increase input in their business. In this case the company must be able to understand the needs and desires of customers. One business that also feels the tight competition is the workshop